If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + (x + 1) = -1(3x + 4) Reorder the terms: 11x + (1 + x) = -1(3x + 4) Remove parenthesis around (1 + x) 11x + 1 + x = -1(3x + 4) Reorder the terms: 1 + 11x + x = -1(3x + 4) Combine like terms: 11x + x = 12x 1 + 12x = -1(3x + 4) Reorder the terms: 1 + 12x = -1(4 + 3x) 1 + 12x = (4 * -1 + 3x * -1) 1 + 12x = (-4 + -3x) Solving 1 + 12x = -4 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 1 + 12x + 3x = -4 + -3x + 3x Combine like terms: 12x + 3x = 15x 1 + 15x = -4 + -3x + 3x Combine like terms: -3x + 3x = 0 1 + 15x = -4 + 0 1 + 15x = -4 Add '-1' to each side of the equation. 1 + -1 + 15x = -4 + -1 Combine like terms: 1 + -1 = 0 0 + 15x = -4 + -1 15x = -4 + -1 Combine like terms: -4 + -1 = -5 15x = -5 Divide each side by '15'. x = -0.3333333333 Simplifying x = -0.3333333333
| -5x+2=11 | | 5-4y+y-1= | | 2h+7h-9=54 | | (6x-11w^2)-(4+7w^2)=0 | | 3x+1=73 | | -3G+6+2g=9 | | 2x^2-15=-x | | 4x-3x^2= | | 8+16=? | | 180=90+4x-7+2x+1 | | (w+2)(w-3)= | | 6x+15=99 | | e=3e-1 | | -40x+(-12x)= | | 2(6-y)=4(2y+2) | | -5(-6n+3)-3=102 | | -66=5x+4x-3 | | 0=X^2-128x-23040 | | x+(x+21)=180 | | -4x+3=35 | | 21e-7=98 | | -15=4x-7-3x-4 | | (g^4+4g)+9g^4+7g= | | 2x+1+4x-9= | | 3x+(x+15)+x=180 | | 4-(y+2)=3y+(y-1) | | -6=n-21 | | 180=3x-1+9x-7+19 | | 2(2y+6)+2y=12 | | 6h+4-3+6h=11 | | (2y-64)+(2y)=180 | | (7y^3-3y^2+4y)+(8y^4+3y^2)= |